Computer game as a tool for machine learning education - Doležel, Petr; Dvořák, Miroslav (IEEE (Institute of Electrical and Electronics Engineers), 2017)
The effective education is one of very important and everlasting challenges of human society. With each generation of students, new approaches have to be implemented to keep the process of education prosperous. This paper introduces a small piece to a set of modern tools for education of Informatics and Electrical Engineering. To be more specific, an interactive software for machine learning testing and demonstration is presented in this paper. The software is designed especially to be used as a motivation and a first encounter to these areas of technical studies, while it supports individual efforts of the students. In the paper, the software architecture is described and, in the second half of the paper, some possibilities of software usage in education process are suggested.
Počítačová hra jako nástroj pro výuku strojového učení
Keywords: Education; machine learning; simulation; Výuka a vzdělávání; strojové učení; simulace